PEMANFAATAN BIOCHAR ASAL CANGKANG KELAPA SAWIT SEBAGAI BAHAN PEMBAWA MIKROBA PEMANTAP AGREGAT - L. P. Santi; D. H. Goenadi (BUANA SAINS, 2012)
The porous structure of biochar promotes ability to absorb soluble organic matter, gases, and inorganic nutrients. These characters are indeed highly suitable habitat for microbes to colonize, grow, and reproduce. A series of research was carried out aiming at to study the possibility of using biochar from palm kernel shell as bio-ameliorant carrier material for aggregate stabilizing microbes and determine the effectiveness of the newly-constructed bio-ameliorant in an Ultisol. Biochar was examined their physicochemical characteristics and the microbes population residing in it over time. Fourier-transformed infrared spectroscopy (FTIR) was used for obtaining vibrational spectra of the biochar that related to promote organo-mineral complexes of functional groups. The results indicate that biochar was suitable carrier material as it has highest total pore spaces and available water content in the newly-constructed bio-ameliorant compared to peat and compost. Microbial population obtained from the granular forms of bio-ameliorant was 107 cfu/g of the sample until 12 months shelve-life periods. Biochar showed intensive bands in the range of 3413-3400/cm corresponding to the stretching band of O-H (hydroxyl) and N-H amine). In the region 1170-950 /cm, bio-char exhibited the absorption characteristic at 1034/ cm corresponding to the existence of O-CH3 vibrations. The best vegetative growth performance of Bisma variety in Ultisol at Experiment Station Taman Bogo, Lampung, was shown by the application of 100% standard dosage of NPK conventional fertilizers in combination with the addition of 4.2 g bio-ameliorant/tree. Yield of dry grain of maize was higher (+15.7%) by application of 100% standard dosage and 2.1 g bio-ameliorant/tree (112 kg/ha) than that obtained by standard dosage of conventional fertilizer